2006
DOI: 10.1002/app.22722
|View full text |Cite
|
Sign up to set email alerts
|

Barrier properties of chlorobutyl nanoclay composites

Abstract: Elastomeric materials are used as barriers to protect workers against exposure to chemicals. The effectiveness of a polymer as a chemical protective material depends on the rate of permeation of chemicals through it. The permeation rate is dependent on the type and amount of fillers added into the polymer matrix. In this study, Chlorobutyl nanoclay composites were prepared by addition of organically modified and unmodified nanoclays at different filler loadings. The nanocomposites were swollen in three solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Even under the best of circumstances exfoliation of organoclays in neat polyolefins like polypropylene, PP, or polyethylene, PE, is not very good and far less than that observed in polyamides, 200 polyurethanes, and some other polar polymers [84,96,101]. It has been found that a small amount of a polyolefin that has been lightly grafted with maleic anhydride, w1% MA by weight is typical, can act as a very effective ''compatibilizer'' for dispersing the organoclay in the parent polyolefin [84,101,103,106,117,118,[143][144][145][146][147][148].…”
Section: Nanocomposite Formation: Exfoliationmentioning
confidence: 98%
See 1 more Smart Citation
“…Even under the best of circumstances exfoliation of organoclays in neat polyolefins like polypropylene, PP, or polyethylene, PE, is not very good and far less than that observed in polyamides, 200 polyurethanes, and some other polar polymers [84,96,101]. It has been found that a small amount of a polyolefin that has been lightly grafted with maleic anhydride, w1% MA by weight is typical, can act as a very effective ''compatibilizer'' for dispersing the organoclay in the parent polyolefin [84,101,103,106,117,118,[143][144][145][146][147][148].…”
Section: Nanocomposite Formation: Exfoliationmentioning
confidence: 98%
“…The moisture vapor transmission, however, did not show any significant change. Exfoliated clay modified chlorobutyl rubber showed decreased diffusion for several organic chemicals suggesting utility for chemical protective gloves/clothing [200]. Exfoliated clay added to polyamide 6/polyolefin (polyethylene or polypropylene) blends yielded an improved barrier to styrene permeation for melt blown films [201].…”
Section: Barrier and Membrane Separation Propertiesmentioning
confidence: 99%
“…It has been observed that during the preparation of the nanocomposites, the obtained aspect ratio depends on the volume fraction. In chlorobutyl/montmorillonite nanocomposites, e.g., the obtained aspect ratio decreases with increasing f, using either modified or nonmodified particles [30]. Obviously, increasing f results in a reduction of the degree of delamination and, consequently, in the reduction of the final particle aspect ratio.…”
Section: Random Spatial Positioning Of Parallel Platesmentioning
confidence: 97%
“…Many elastomers have been utilized to attempt to form nanocomposites with high barrier properties, including NR [272,[289][290][291], SBR [292], NBR [281,293], HNBR [278], butadiene rubber (BR) [294], EPDM [281], isobutene-isoprene rubber (IIR) [279,285,295], CR [296], chlorinated isobutene-isoprene rubber [280], FKM [297], and PU [276,298].…”
Section: Materials Systems For the Elastomer Nanocomposites With Lomentioning
confidence: 99%